Optimalisasi Halal Value Chain dalam Mendukung Penguatan Ekonomi Syariah di Sektor Industri Kreatif - Feni Apriliyani; Anton Sudrajat; Ayus Ahmad Yusuf (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the optimization of the halal value chain as a strategic instrument in strengthening the Islamic economy within the creative industry sector. The urgency of this research is grounded in the significant potential of the creative industry, which has not yet been fully integrated with halal principles in a comprehensive manner, spanning from upstream to downstream processes, including production, distribution, and marketing. This study employs a qualitative approach with a descriptive-analytical design. Data were collected through observation, in-depth interviews, and documentation, and were systematically analyzed to identify the level of halal value chain implementation as well as the factors influencing its effectiveness. The findings indicate that the optimization of the halal value chain plays a significant role in enhancing the competitiveness of the sharia-based creative industry, particularly in ensuring product halalness, strengthening consumer trust, and expanding market access. However, its implementation still faces several challenges, including limited halal literacy among business actors, suboptimal halal certification processes, and weak integration of the supporting ecosystem. Therefore, multi-stakeholder synergy among business actors, government, and related institutions is essential in strengthening regulations, improving literacy, and facilitating halal certification. This study is expected to contribute both academically and practically to the development of the Islamic economy through the sustainable strengthening of the halal value chain in the creative industry sector.